(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Patients with chronic liver disease (CLD) are increasing aware of the consequence of osteoporosis. Low bone turnover, impaired osteoblast function, and low blood osteocalcin levels are the hallmarks of osteoporosis in CLD, which mostly affects trabecular bone. Osteoporosis is the public health issue of metabolic bone disease among the every age group throughout the globe especially in Pakistan. The current study was conducted in DHQ, KPK, Pakistan to determine the prevalence percentage of osteoporosis in patients during July 2020-2021. Out of 548 patients, the prevalence of osteoporosis was 22.9% at a 95% Confidence Interval (5.9-12.5%), which was higher among female (57.60%) than male (42.40%). The higher prevalence rate was recorded in old patients than young patients. The lower weight, height and cholestasis in sex are risk factors of osteoporosis in chronic liver disease. The early detection of disease can help in decreasing the socio-economic burden and fracture rates.